Identification and Exploration of Lecithin from Novel Sources and its Applications - Balaguru, S.; Ramya Devi, D.; Vedha Hari, B.N. (Asian Journal of Chemistry, 2014)
Recent research on natural sources such as plants, microbes and other naturally derived compounds have grabbed much attention because of their reduced side effects in treating various ailments and biocompatibility. Technological advancements in the field of medicine have additionally triggered the researchers in developing novel systems for the treatment of many diseases among which cancer research has gained much importance in recent years. Lecithin, a naturally occurring compound present in egg yolk, soya bean oil and milk possess significant anticancer and antioxidant activity. It is composed of phospholipids, fatty acids, carbohydrates and a major constituent of phosphatidylcholine molecule, which is responsible for the normal functioning of nerve cells and cell membranes. The objective of the present work is to extract lecithin compound from Quail’s egg using chemical extraction and its characterization using thin layer chromatography, gas chromatography-mass spectroscopy and nuclear magnetic resonance spectroscopy for the structural elucidation of various constituents present in the crude lecithin. Further, the extracted crude lecithin has been assayed for cytotoxic activity in normal cell line using MTT assay.